Adaptive Modulation for multiantenna transmissions with channel mean feedback. - Shengli Zhou
Adaptive modulation has the potential to increase the system throughput significantly by matching transmitter parameters to time-varying channel conditions. However, adaptive modulation schemes that rely on perfect channel state information (CSI) are sensitive to CSI imperfections induced by estimation errors and feedback delays. In this paper, we design adaptive modulation schemes for multiantenna transmissions based on partial CSI, that models the spatial fading channels as Gaussian random variables with nonzero mean and white covariance, conditioned on feedback information. Based on a two-dimensional beamformer, our proposed transmitter optimally adapts the basis beams, the power allocation between two beams, and the signal constellation, to maximize the transmission rate, while maintaining a target bit-error rate. Adaptive trellis-coded multiantenna modulation is also investigated. Numerical results demonstrate the rate improvement, and illustrate an interesting tradeoff that emerges between feedback quality and hardware complexity.
Keywords: Gaussian random variable; Adaptive trellis-coded multiantenna modulation; Bit error rate; Channel mean feedback; Channel state information; Estimation errors; Feedback delays; Hardware complexity; Matching transmitter parameters; Multiantenna transmissions; Power allocation; Signal constellation; Spatial fading channel; Time-varying channel condition; Transmitter; Two-dimensional beamformer